Motor hub capable of being prevented from falling into deep pit to be fractured - CHEN KE (2022)
The invention belongs to the technical field of automobile hubs, and particularly relates to a motor hub capable of preventing falling into a deep pit to break, which comprises a hub motor, a rim is mounted outside the hub motor, spokes are mounted on one side, away from an automobile, of the hub motor, and a plurality of buffer strips are slidably connected into the rim. Buffer strips are arranged on the rim, a buffer air bag is arranged between the buffer strips and the rim, the multiple buffer strips are distributed in an array shape, multiple balance weight balls are arranged in the buffer air bag, elastic pieces are fixed between the buffer air bag and the multiple balance weight balls, and the side, away from the center of the rim, of the buffer air bag is connected with a ventilation pipe through a hose. The ventilation pipe is connected with the rim in a penetrating mode, and a one-way valve is installed in the ventilation pipe. Through the design of the buffer strip and the buffer air bag, when the r